Evaluation of the Implementation of the Saturday Fast Service Program (Lepat Ketan) as a Local Innovation in Padang Panjang Barat Subdistrict - Egi Zulfarayani; Ria Ariany; Roni Ekha Putera (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
This study evaluates the implementation of the Saturday Fast Service Program, known as Lepat Ketan, at the Padang Panjang Barat Subdistrict Office as a local public service innovation. The program was established to provide administrative services outside regular working days for citizens who experience time constraints from Monday to Friday. The research problem emerged because service utilization declined sharply from late 2024 to 2025, while a specific evaluation of the program sustainability had not been conducted. This study applies a descriptive qualitative approach using the CIPP evaluation model, which covers context, input, process, and product. Data were collected through interviews, observation, and documentation involving subdistrict officials, service implementers, and service users. The findings show that, in terms of context, the program was initially relevant to community needs, but the demand for Saturday services did not occur regularly every week. In terms of input, the program had human resources and policy legitimacy, but budget support, technical procedures, and operational arrangements were not adequate. In terms of process, the implementation initially worked and provided benefits, but consistency weakened due to low user demand, tiered administrative coordination, and budget efficiency measures. In terms of product, the target of providing routine services every Saturday was not achieved because service utilization fell from 67 Saturday service cases in 2024 to only one case between January and May 2025. The study concludes that Lepat Ketan should not be maintained as a weekly routine service. Instead, it should be redesigned as a conditional additional service based on appointments, verified demand, tiered coordination, service records, and periodic evaluation.